PRECEDE-PROCEED Theory Regarding Socio-Cultural Aspects that Influence the Treatment of Healthy Reproduction Organs among Senior High School Female Students in Surakarta - Santy Irene Putri; RB Soemanto; Yulia Lanti Retno Dewi (Journal of Health Promotion and Behavior, 2017)
Background: The group that has been vulnerable to the abandonment of reproductive health rights in Indonesia is adolescents. The lack of adolescents’ awareness toward their behaviors in maintaining genital organs cleanliness is due to socio-cultural limitations might cause negative impact toward their reproductive health. This study aimed at analyzing the socio-cultural aspects that influenced the behaviors in treating healthy reproductive organs among female senior high school students in the City of Surakarta.Subjects and Method: This was a mixed-method study with quantitative and qualitative approach. This study was conducted in State Senior High School 1, Al-Islam 1 Senior High School and Regina Pacis Senior High School; all of these senior high schools were located in the City of Surakarta, from February to March 2017. A total of 120 subjects were selected by stratified random sampling. In addition, the sample also included 5 mothers and fathers who had been selected by purposive sampling. The dependent variable was the behaviors in treating reproductive organs. The independent variables were knowledge toward reproduction organ health, family support, toilet/ bathroom availability, clean water availability, culture and information exposure. The dependent and independent variables were collected by a set of questionnaire and analyzed by path analysis. The qualitative data were collected by in-depth interview and analyzed by Miles Huberman method.Results: The behaviors in treating reproductive organ were influenced by good knowledge (b= 0.21; SE= 0.09; p= 0.020), high information exposure (b= 0.20; SE= 0.07; p= 0.005), positive culture (b= 0.15; SE= 0.07; p= 0.039), toilet/ bathroom availability (b= 0.21; SE= 0.07; p= 0.026), clean water availability (b= 0.14; SE= 0.08; p= 0.073) and strong family support (b= 0.16; SE= 0.08; p= 0.041). Then, the knowledge of reproductive health was influenced by high information exposure (b= 0.31; SE= 0.07; p<0.001) and positive culture (b= 0.16; SE= 0.07; p= 0.016).Conclusions: The behaviors in treating reproductive organs are influenced by good knowledge, high information exposure, positive culture, toilet availability, clean water availability and strong family support. The knowledge of reproductive health are influenced by high information exposure and positive culture.Keyword: precede-proceed, path analysis, socio-culture, reproductive healthCorrespondence: Santy Irene Putri. Masters Program in Public Heath, Sebelas Maret University, Surakarta. Email: santyireneputri@yahoo.co.id. Mobile: +6285785836884.Journal of Health Promotion and Behavior (2017), 2(1): 27-40https://doi.org/10.26911/thejhpb.2017.02.01.03